Psychological, anthropological, sociological foundations of education - Tulio, Doris D. (Mandaluyong City, Philippines : National Book Store, 2008)
The book Psychological, Anthropological, and Sociological Foundations of Education written in style that students will find readable, provides them with important insights into education and professional opportunities that exist for knowledge and dedicates educators. It is instructive to see how the psychologist, anthropologist, sociologist, and other developmentalists have addressed and enhanced noteworthy developments in their perspective ares.
Part I. Psychological foundations of education -- 1. The Empirical beginnings and basic contents of educational psychology -- 2. Schools of psychology and motivation -- 3. Personality Theory -- 4. The Teacher, The learner, and The Learning process: a trilogy of effective teaching -- Part II. Anthropology foundations of education -- 5. The History and prospect of anthropology -- 6. Cultural anthropology -- 7. Cultural and personality -- Part III. Sociological foundations of education -- 8. The Role and scope of sociology -- 9. Education and life: a social process.
Includes bibliographical references and index.
Keywords: EDUCATION -- PSYCHOLOGY